Does the state of public health explain the judgment of the voter? - Oliveira, Adriano Oliveira (2017)
Through quantitative surveys carried out in the cities of Recife, Maceió and Santa Cruz do Capibaribe and the statistical test of Chi-square, we show an association between the voters' judgments regarding the mayor's management and the evaluation of the health service. This means that mayors who take care of health create suitable conditions for their re-election. This article reveals that spontaneous identification by the voter of the main problem of the municipality is not relevant to decipher the reasons that motivate him to judge the mayor. However, identifying the problem spontaneously in the universe of health service users is relevant to deciphering the reasons for the judgment of the mayor's management.